2023
DOI: 10.3390/molecules28041527
|View full text |Cite
|
Sign up to set email alerts
|

Niobium: The Focus on Catalytic Application in the Conversion of Biomass and Biomass Derivatives

Abstract: The world scenario regarding consumption and demand for products based on fossil fuels has demonstrated the imperative need to develop new technologies capable of using renewable resources. In this context, the use of biomass to obtain chemical intermediates and fuels has emerged as an important area of research in recent years, since it is a renewable source of carbon in great abundance. It has the benefit of not contributing to the additional emission of greenhouse gases since the CO2 released during the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 237 publications
1
9
0
Order By: Relevance
“…Second, the introduction of Nb (V), which has a unique electronic and energy band structure, provided H[Nb]ZSM-5 with the abilities to generate aromatics via direct phenol deoxygenation, similar to the formation of aromatics observed over CoO/MoO 3 [ 17 ]. This also agrees with literature that reports niobium oxide-based catalysts are effective in catalytic cleavage of C–O bonds [ 31 , 32 ]. In conclusion, the synergistic catalytic effect of Nb (V) and HZSM-5 could cleave both sp 2 and sp 3 C–O–C linkages of lignin vapors and further transform the resultant oxygenates into aromatics via deoxygenation, thus improving the selectivity of monocyclic aromatic products.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Second, the introduction of Nb (V), which has a unique electronic and energy band structure, provided H[Nb]ZSM-5 with the abilities to generate aromatics via direct phenol deoxygenation, similar to the formation of aromatics observed over CoO/MoO 3 [ 17 ]. This also agrees with literature that reports niobium oxide-based catalysts are effective in catalytic cleavage of C–O bonds [ 31 , 32 ]. In conclusion, the synergistic catalytic effect of Nb (V) and HZSM-5 could cleave both sp 2 and sp 3 C–O–C linkages of lignin vapors and further transform the resultant oxygenates into aromatics via deoxygenation, thus improving the selectivity of monocyclic aromatic products.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, the aromatic product contents obtained in our work were compared with those elsewhere in the literature where lignin was pyrolyzed through a similar or identical experimental device under similar conditions [ 31 , 32 ] ( Table 6 ). The total aromatic hydrocarbon yield obtained from H-ZSM-5 in this study was approximately 35.5%, which is consistent with values reported in the literature (32% in ref.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In this sense, niobium based oxides may be promising acid catalysts since they may be relatively water-tolerant 48,49 for various biomass conversion routes 50 involving reactions such as dehydration, 49,[51][52][53] etherification, alcoholysis, 54 acetalization, 55 hydrolysis and esterification. 56,57 According to the literature, niobium oxides may possess Brønsted and Lewis acidity capable of activating carbon-oxygen bonds and oxygencontaining functional groups, 58 accounting for superior performances compared to those of other metal oxides such as MgO, CaO, MgAl hydrotalcites, Al 2 O 3 , and ZrO 2 in Fur/4-heptanone condensation. 59 Zeolites were modified with niobium in order to trigger Fur condensation, 60 and a preliminary study showed good catalytic potential of niobium oxide nanoparticles wrapped within a mesoporous silica component.…”
Section: Introductionmentioning
confidence: 99%